2014
DOI: 10.1074/jbc.m114.570242
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine, a Modulator of Human Translesion DNA Polymerase Activity

Abstract: Background: DNA polymerase is a specialized, error-prone DNA polymerase capable of synthesis past bulky DNA adducts. Results: Sphingosine and sphinganine stimulate the activity of Pol . Conclusion: Sphingosine modulates DNA lesion bypass in addition to controlling cell proliferation following DNA damage. Significance: There are no known stimulators of DNA polymerases. Stimulation by sphingosine represents a novel mode of modulating Pol activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Sphingosine also regulates nuclear lipid signaling as it has been shown to bind the nuclear receptor, Steroidogenic Factor-1, that mediates steroid biosynthesis and primase that regulates synthesis of RNA primers (Simbulan et al 1994;Urs et al 2006). Recently, sphingosine has been found to activate translesion DNA polymerase to promote cell proliferation (Kamath-Loeb et al 2014). Moreover, the cellular effects of sphingosine are cell type and cell context dependent.…”
Section: Sphingolipid Metabolismmentioning
confidence: 98%
“…Sphingosine also regulates nuclear lipid signaling as it has been shown to bind the nuclear receptor, Steroidogenic Factor-1, that mediates steroid biosynthesis and primase that regulates synthesis of RNA primers (Simbulan et al 1994;Urs et al 2006). Recently, sphingosine has been found to activate translesion DNA polymerase to promote cell proliferation (Kamath-Loeb et al 2014). Moreover, the cellular effects of sphingosine are cell type and cell context dependent.…”
Section: Sphingolipid Metabolismmentioning
confidence: 98%
“…First, in vitro experiments suggested that some lipid species, such as oleic acid, may directly bind to DNA (Zhdanov et al, 2002), which could have significant impacts on gene expression but is not currently supported by data obtained under physiological conditions (Fernandes et al, 2018). There is also some evidence supporting an effect of specific lipid species on DNA polymerase activity (Novello et al, 1975;Kamath-Loeb et al, 2014). Interestingly, although the mechanism remains unclear, changes in palmitate concentration in vitro appear to regulate the expression of neuronal genes and increased intracellular palmitate results in increased differentiation of neural precursor cells into neurons (Ardah et al, 2018).…”
Section: Lipids and Regulation Of The Transcriptome And Epigenomementioning
confidence: 99%
“…This technique has been applied to study a number of systems including D-3-phosphoglycerate dehydrogenase, 45 beta-site amyloid precursor protein-cleaving enzyme, 46 ATP-phosphoribosyl-transferase, 47 DNA polymerase γ , 48 and HIV-RT. 49,50 …”
Section: Resultsmentioning
confidence: 99%
“…Presteady-state kinetic analysis of enzyme inhibition is a powerful approach for determining which step or steps are affected by a given inhibitor. This technique has been applied to study a number of systems including D-3-phosphoglycerate dehydrogenase, 45 beta-site amyloid precursor protein-cleaving enzyme, 46 ATP-phosphoribosyltransferase, 47 DNA polymerase γ, 48 and HIV-RT. 49,50 Presteady-state analysis was carried out using a rapid quench apparatus to further characterize the mechanism of inhibition of pol β and pol λ.…”
Section: ′-G a A G A C T G G T G A A G A C T T G A G T A C A G G T C ...mentioning
confidence: 99%